Insights into the performance and kinetics of face mask-derived nitrogen-doped porous carbon as peroxymonosulfate activator for gatifloxacin removal. (December 2022) - Ng, Wen-Yih; Choong, Zheng-Yi; Gasim, Mohamed Faisal; Khoerunnisa, Fitri; Lin, Kun-Yi Andrew; Oh, Wen-Da
Abstract: The outbreak of COVID-19 has led to the increase in face mask waste globally. In this study, face mask-derived carbocatalysts doped with nitrogen (N-Mask) were fabricated through one-step pyrolysis of 1:5 w/w mixture of face mask and urea at different temperatures to activate peroxymonosulfate (PMS) for gatifloxacin (GAT) degradation. The N-Mask prepared at 800 °C (N-Mask800) exhibited the highest GAT degradation rate with k app = 0.093 min −1 which could be attributed to its high N doping level (17.1 wt%) and highest specific surface area (237.13 m 2 g −1 ). The relationship between k app, catalyst loading and PMS dosage at various pHs on GAT degradation were successfully established. It was also found that the GAT degradation rate was inhibited in the sequential operating mode compared to the simultaneous operating mode. It was construed that adsorption and catalysis share the same active sites. Deterioration in catalytic performance was observed over successive cycles due to the surface chemistry change during catalysis, and difficulty in catalyst recovery after treatment. Radical scavenger study revealed that both radical and nonradical pathways were involved during GAT degradation, with nonradical pathway playing a dominant role. XPS analysis revealed that pyrrolic N and graphitic N can facilitate PMS activation via radical and nonradical pathways. Based on the LC-MS/MS analysis, the GAT degradation intermediates were identified, and the possible degradation pathways were tentatively proposed. Overall, this study demonstrated that carbocatalyst derived from face mask could be transformed into cost-effective and environmentally friendly PMS activator for environmental wastewater treatment applications. Graphical abstract: Unlabelled Image Highlights: Face mask was employed as precursor to prepare nitrogen-doped porous carbon (N-mask). N-Mask calcined at 800 °C exhibited highest pollutant removal rate at k app = 0.093 min −1 . Kinetic models correlating k app, catalyst loading, PMS dosage and pH was established. Change in at.%. of graphitic N and pyrrolic N signifies their involvement in PMS activation. Total of six GAT intermediates was identified, and their degradation pathways were proposed.